(untitled) (Research, Society and Development, 2022)
Observing the market need and the benefits of medicinal plants for centuries, the present research aimed to analyze the yield, phytochemical screening, quantification of total phenolic compounds and the antioxidant capacity generated by plant extracts from the leaves of the female Syzygium cumini. In S. cumini, the yield of the aqueous extract (3.886a ± 0.06145) and ethanolic extract (9.087b ± 0.2118) was determined, where the efficiency of the ethanolic solvent in the extraction process by maceration was noted, it can be considered the ability to scavenge free radicals that are influenced by the method and solvent used. The quantification of total phenolic compounds in the extracts was performed by the Folin-Ciocalteau method, in which the aqueous extract resulted in 327.51 mg EAT.g-1 and the ethanolic extract 397.65 mg EAT.g-1, thus showing form a greater amount of phenol content, in the continuity of this research, a phytochemical search was also carried out, where several secondary metabolites such as alkaloids, flavanoids, saponins, coumarins, tannins and phenols were presented. The method to assess antioxidant activity was the ABTS, this assay is based on the potential of the antioxidants present to reduce ABTS●+ to ABTS, in this way there is a change in color from blue-green to colorless. The leaves showed a greater amount of phenolic compounds and greater free antiradical activity found in the extracts. It is understood that the researched extracts from the leaves of S. cumini known as jambolão presented chemical composition based on the content of total phenolic compounds, secondary metabolites, antioxidant capacity by the ABTS method.